Flexible self-healing phase change film with high transition enthalpy for thermal management. (June 2023) - Deng, Chengxin; Dong, Hongsheng; Kou, Yan; Liu, Hanqing; Sun, Keyan; Jian, Weiwei; Shi, Quan
Abstract: Thermal management using phase change materials (PCMs) is a promising option for guarantying safety and mitigating hazards of related processes involved significant amounts of heat. However, the intrinsic rigidity, easy brittle failure and non-recyclability of currently used PCMs lead to poor mutual contact, high thermal contact resistance and short service life in practical applications. To overcome these issues, this study has developed a flexible self-healing phase change film with high transition enthalpy by in-situ incorporating erythritol into hydrogen-bonded networks constructed with polyvinyl alcohol (PVA) and polyvinylpyrrolidine (PVP). The phase change film behaves an outstanding flexibility with the high phase transition enthalpy up to 191.5 J/g at the transition temperature of 98.7 °C. Remarkably, owing to the reversibility of hydrogen bonds, the flexible phase change film can exhibit an attractive self-healing ability with the healing efficiency as high as 91.1 %. In addition, the phase change film has been attached to the surface of a heating platform to evaluate its potential to thermal management. The results indicate that this flexible self-healing phase change film can maintain an efficient capability of thermal management at different heating rates, showing great potentials for the development of advanced thermal management technology. Highlights: A flexible self-healing phase change film used for thermal management is reported. The film behaves outstanding flexibility with transition enthalpy of 191.5 J/g. The self-healing efficiency of the film can be achieved as high as 91.1 %. The film can maintain an efficient capability of thermal management.